In situ fabrication of MIL-68(In)@ZnIn2S4 heterojunction for enhanced photocatalytic hydrogen production. Issue 5 (18th January 2023) - Tan, Mengxi; Yu, Chengye; Zeng, Hua; Liu, Chuanbao; Dong, Wenjun; Meng, Huimin; Su, Yanjing; Qiao, Lijie; Gao, Lei; Lu, Qipeng; Bai, Yang
Abstract : The type II heterojunction MIL-68(In)@ZIS with hierarchical loose structure is successfully synthesized by in-situ growth. The optimized photocatalyst shows an excellent photocatalytic performance of 9.09 mmol g −1 h −1  with great stability. Abstract : Metal–organic frameworks (MOFs), as a class of semiconductor-like materials, are widely used in photocatalysis. However, the limited visible light absorption and poor charge separation efficiency are the main challenges restricting their photocatalytic performance. Herein, the type II heterojunction MIL-68(In)@ZIS was successfully fabricated by in situ growth of ZnIn2 S4 (ZIS) on the surface of a representative MOF, i.e. MIL-68(In). After composition optimization, MIL-68(In)-20@ZIS shows an extraordinary photocatalytic hydrogen production efficiency of 9.09 mmol g −1 h −1 and good photochemical stability, which far exceeds those of most photocatalysts. The hierarchical loose structure of MIL-68(In)-20@ZIS is conducive to the adsorption of reactants and mass transfer. Meanwhile, a large number of tight 2D contact interfaces significantly reduce the obstruction of charge transfer, paving the way for high-perform photocatalytic hydrogen evolution. The experimental results demonstrate that the MIL-68(In)@ZIS heterojunction achieves intensive photoresponse and effective charge separation and transfer benefiting from unique charge transport paths of a type II heterojunction. This study opens an avenue toward MOF-based heterojunctions for solar energy conversion.